Salivary IL-10 and TNF-α levels in Dental Caries Detection in Pediatric β-Thalassemia Major Patients - Ban Hazem Hassan - Zainab Abduljabbar Athab ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
β-Thalassemia Major, a severe genetic blood disorder, necessitates lifelong blood transfusions and can lead to various complications, including oxidative stress and dental caries. This study aims to evaluate the salivary levels of cytokines Interleukin-10 (IL-10) and Tumor Necrosis Factor-alpha (TNF-α) in pediatric β-thalassemia Major patients and their association with dental caries. With 80 participants aged 8-12, split equally between patients and healthy controls, it found significantly higher cytokine levels in patients, indicating an altered immune response. Despite higher dental caries severity in patients, no significant correlation with cytokine levels was noted. The findings underscore the necessity for specialized dental care for β-thalassemia Major patients due to their increased risk of dental caries, highlighting the potential impact of their condition on oral health.